Large T antigen mediated target gene replication improves site-specific recombination efficiency - Wang, Zening; Chen, Chuan; Ge, Xin (Frontiers in Bioengineering and Biotechnology, 2024)
With advantages of high-fidelity, monoclonality and large cargo capacity, site-specific recombination (SSR) holds great promises for precise genomic modifications. However, broad applications of SSR have been hurdled by low integration efficiency, and the amount of donor DNA available in nucleus for SSR presents as a limiting factor. Inspired by the DNA replication mechanisms observed in double stranded DNA virus SV40, we hypothesized that expression of SV40 large T antigen (TAg) can increase the copy number of the donor plasmid bearing an SV40 origin, and in consequence promote recombination events. This hypothesis was tested with dual recombinase-mediated cassette exchange (RMCE) on suspension 293F cells. Results showed that TAg co-transfection significantly enhanced SSR in polyclonal cells. In the monoclonal cell line carrying a single landing pad at an identified genomic locus, 12% RMCE efficiency was achieved, and such improvement was indeed correlated with donor plasmid amplification. The developed TAg facilitated RMCE (T-RMCE) was amenable to construct large libraries of >107 diversity, from which GFP variants with enhanced fluorescence were isolated. We expect the underlying principle of target gene amplification can be applicable to other SSR processes and gene editing approaches in general for directed evolution and large-scale genomic screening in mammalian cells.